2018
DOI: 10.15343/0104-7809.2018420198122
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adolescents’ diet with the Dietary Guidelines for the Brazilian Population

Abstract: Adolescence is characterized by the transition period between childhood and adulthood. The evaluation of dietary habits at this stage provides ground for the implementation of prevention policies of chronic noncommunicable diseases. The aim of this study was to describe the eating habits of adolescent students from two technical schools in the eastern zone of the city of São Paulo and compare them with the Dietary Guidelines for the Brazilian Population. All incoming students of 2017, of both sexes, up to 19 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Other studies carried out in Brazil and Singapore also indicate that a significant proportion of children and adolescents do not consume fresh foods daily, such as fruits and vegetables or minimally processed foods, such as rice and beans. 17 , 18 , 19 In contrast, the prevalence of daily consumption of UP foods by adolescents in São Paulo was 64 %, and of soda 16.2 %, in 2017; this study also showed a negative association between participation in food purchases and soda consumption; regular cooking was positively associated with the consumption of rice and beans. 17 In the study conducted on 44 children in Diamantina, state of Minas Gerais, when evaluating lunch boxes, the UP foods were predominant, especially: yogurt (55.88 %); boxed chocolate milk (41.18 %); sandwich cookies and snacks (50 % and 35.29 %, respectively).…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Other studies carried out in Brazil and Singapore also indicate that a significant proportion of children and adolescents do not consume fresh foods daily, such as fruits and vegetables or minimally processed foods, such as rice and beans. 17 , 18 , 19 In contrast, the prevalence of daily consumption of UP foods by adolescents in São Paulo was 64 %, and of soda 16.2 %, in 2017; this study also showed a negative association between participation in food purchases and soda consumption; regular cooking was positively associated with the consumption of rice and beans. 17 In the study conducted on 44 children in Diamantina, state of Minas Gerais, when evaluating lunch boxes, the UP foods were predominant, especially: yogurt (55.88 %); boxed chocolate milk (41.18 %); sandwich cookies and snacks (50 % and 35.29 %, respectively).…”
Section: Resultsmentioning
confidence: 50%
“…Maternal ethnicity, religion and level of schooling were significantly and independently associated with the co-occurrence of NCD risk factors. Nicolau et al 17 (2018) Cross-sectional 111 incoming students from all Integrated Technical High School Courses in 2017, of both sexes, up to 19 years old. To characterize the diet of adolescent students from two technical schools in the east zone of the city of São Paulo according to the GAPB An important number of the adolescents do not consume fresh foods (fruits, vegetables) or minimally processed foods (rice and beans) daily.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation